PENGGUNAAN PLATFORM E-LEARNING DALAM PERKULIAHAN DAN DAMPAKNYA TERHADAP PENDAMPINGAN MAHASISWA SEBAGAI CALON PEKERJA PASTORAL DI STAKAT NEGERI PONTIANAK - Lumban Tobing, Ona Sastri (STP St. Bonaventura Medan, 2022)
Research with the theme above is the result of research motivated by the influence of the Covid-19 pandemic situation, which resulted in a change from the offline to online lecture system. This has an impact on the student mentoring process at Pontianak State STAKat. Routine spiritual life assistance activities by lecturers which are usually carried out every day in the morning have been stopped since the pandemic until we are now entering our 3rd year without direct face-to-face contact. The reality is that the influence of this shift in the learning system means that the lecture process is not completely optimal. The aim of this research is to find out and explore how lecturers at STAKat Negeri Pontianak can use e-learning, what e-learning platforms are used, the applications, what are the obstacles, and whether the final goal of teaching is conveyed to the target (students)? This research uses a qualitative approach. The informants in this research were lecturers at the Pontianak State STAKat. The lecture process, which was initially carried out offline, especially as a university that produces candidates for Catholic Religion Teachers, Catechists, is an effort to form prospective pastoral workers who are knowledgeable and faithful, have good behavior, not just make people smart. In the lecture process which has been taking place online for the last 3 years or so, it is hoped that the knowledge conveyed is not just known and studied, but is truly understood and applied in everyday life in real action. Therefore, prospective pastoral workers must continue to experience the process of forming or developing themselves through spiritual life assistance. The findings from the results of this research are that even in the midst of the Covid-19 pandemic situation, lecturers, especially Catholic lecturers in the role, are trying as hard as possible to learn using e-learning applications, carrying out lectures while still paying attention to all cognitive aspects and spiritual life support for prospective pastoral workers